Physical mapping of a DNA sequence common to plasmids of incompatibility group F I. - Palchaudhuri, S (1977)
We have mapped a region of homology within a 2.2 kilobase segment of plasmids of incompatibility group F I, WHICH IS CONTAINED IN AN EcoRI restriction enzyme fragment bearing genes for autonomous replication; The coordinates of the 2.2 kilobase segment are 46.4F-48.6F on the physical map of the F plasmid. The orgin of vegetative replication has been mapped at 42.5F, at which site F has no sequence homology with other group F I plasmids. Plasmids belonging to other incompatibility groups have no homology with the 46.4-48.6 F segment. Possible mechanisms underlying incompatibility are discussed. We think that incompatibility is due to either a limitation in a common equipartitioning mechanism or a limitation in a common replication control. In either case, the common mechanism is specific for plasmids belonging to a given incompatibility group.